Religious Moderation between Balinese Hindus and Sasak Muslims at Lingsar Temple: A Theo-Humanist Perspective - Ni Luh Sinar Ayu Ratna Dewi; I Wayan Wirata; Nanang Sutrisno (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This article aims to reveal the phenomenon of religious moderation between Balinese Hindus and Sasak Muslims at the shared sacred space of Lingsar Temple in the Muslim-dominated island of Lombok (east of Bali) from a theo-humanist perspective. It addresses how theology, as the foundation of religious belief, can be transformed into humanistic practices that foster religious moderation in everyday interactions. Using a qualitative ethnographic approach grounded in hermeneutics, phenomenology, and social construction theory, data were collected through observation, in-depth interviews, and document analysis, and interpreted through reflective analysis. This study finds that theo-humanism functions as a central social mechanism in realizing religious moderation at Lingsar Temple through two interrelated processes: the construction of a shared sacred space and the transformation of theological awareness into lived social harmony. Theo-humanism translates abstract theological doctrines into empirical social practices through three Bergerian moments—externalization, objectivation, and internalization—reproduced and sustained across generations, enabling theological plurality to be continuously negotiated as practical interreligious coexistence.